On (𝑁,𝑝,𝑞)(𝐸,1) Summability of Fourier Series - H. K. Nigam; Ajay Sharma (International Journal of Mathematics and Mathematical Sciences)
A new theorem on (𝑁,𝑝,𝑞)(𝐸,1) summability of Fourier series has been established.